2003
DOI: 10.2133/dmpk.18.71
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Research on Inter-racial Difference in Drug Metabolism II. Analysis on Relationship between Enzyme Activities of CYP2D6 and CYP2C19 and their Relevant Genotypes

Abstract: The enzyme activities of CYP2D6 and CYP2C19 show a genetic polymorphism, and the frequency of poor metabolizers (PMs) on these enzymes depends on races. We have analyzed frequencies of mutant alleles and PMs based on the published data in previous study (Shimizu, T. et al.: Bioinformatics research on inter-racial difference in drug metabolism, I. Analysis on frequencies of mutant alleles and poor metabolizers on CYP2D6 and CYP2C19.). The study shows that there were racial differences in the frequencies of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…We also did not evaluate CYP2C19 status, where poor metabolizers have been shown to have lower VPCs (12,30). The frequency of poor CYP2C19 metabolizers was reported to be significantly higher in Asians (15% to 20%) than in Caucasians (2% to 3%), and in this study, none of the included patients was of Asian origin (31). Further, some previously described factors, such as concomitant PPI treatment, were present in the vast majority of included patients, while other factors, such as concomitant phenytoin or rifampin medication, were present in very few.…”
Section: Discussionmentioning
confidence: 77%
“…We also did not evaluate CYP2C19 status, where poor metabolizers have been shown to have lower VPCs (12,30). The frequency of poor CYP2C19 metabolizers was reported to be significantly higher in Asians (15% to 20%) than in Caucasians (2% to 3%), and in this study, none of the included patients was of Asian origin (31). Further, some previously described factors, such as concomitant PPI treatment, were present in the vast majority of included patients, while other factors, such as concomitant phenytoin or rifampin medication, were present in very few.…”
Section: Discussionmentioning
confidence: 77%
“…Genetic polymorphism and phenotypic studies have shown that PMs account for approximately 7.7% among Caucasians, but only approximately 1% among Asians . IMs are mainly distributed in Asian populations; for example, CYP2D6*10, a common gene mutation in Chinese individuals, has a frequency as high as 64%‐70% . In contrast, in Caucasians, CYP2D6 IM has a population frequency of <0.5% .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…In addition, carriers of reduced activity alleles are termed intermediate metabolizers (IM) and exhibit a rate of metabolism between that of EM and PM, and ultrarapid metabolizers (UM) usually carry multiple copies of functional alleles and produce excess enzymatic activity. These four main phenotypes occur with varying prevalence in populations of different ethnic or geographic origin [2][3][4] .…”
mentioning
confidence: 99%